Stigmergic hyperlink:a new social web object - Marques, Artur (2011)
Inspired by patterns of behavior generated in social networks, a prototype of a new object was designed and developed for the World Wide Web – the stigmergic hyperlink or “stigh”. In a system of stighs, like a Web page, the objects that users do use grow “healthier”, while the unused “weaken”, eventually to the extreme of their “death”, being autopoieticaly replaced by new destinations. At the single Web page scale, these systems perform like recommendation systems and embody an “ecological” treatment to unappreciated links. On the much wider scale of generalized usage, because each stigh has a method to retrieve information about its destination, Web agents in general and search engines in particular, would have the option to delegate the crawling and/or the parsing of the destination. This would be an interesting social change: after becoming not only consumers, but also content producers, Web users would, just by hosting (automatic) stighs, become information service providers too.